La aplicación del currículo de educación inicial y su incidencia en el desarrollo psicomotriz de los niños y niñas del nivel i de la escuela “Gran Colombia” de la ciudad de Alamor, provincia de Loja. Período lectivo 2013–2014”. Lineamientos alternativos - Alvarado Alvarado, Magali María (2016)
This research titled: "THE APPLICATION OF INITIAL EDUCATION CURRICULUM AND ITS IMPACT ON DEVELOPMENT PSYCHOMOTOR CHILDREN OF SCHOOL LEVEL I" GRAN COLOMBIA "ALAMOR CITY, province of Loja. LECTIVO PERIOD 2013-2014 ". Alternative guidelines. It is structured based on the current Guidelines Graduation at the National University of Loja. The central issue raised in this research was: Having analyzed the research question posed in the following terms: How affects the initial basic education curriculum in the psychomotor development of children of the Initial Level I School "Gran Colombia" Alamor city, province of Loja. School period 2013-2014 ?.The general objective that guided the research process was: to determine the incidence of initial education curriculum in the psychomotor development of children Initial Level I schools "Gran Colombia" Alamor City, Province of Loja. Lectivo period 2013 - 2014 The methods used were scientific, inductive, deductive, analytic-synthetic and descriptive statistical model. The techniques used were: Survey applied to teachers of School First Grade "Gran Colombia" Alamor city to establish the Implementation of initial education curriculum in the daily work with children .; and recorded on an observation applied to children to children Initial Level I schools "Gran Colombia" to assess psychomotor development. Application of the teachers Survey found that: 100% of teachers do apply the initial education curriculum in the daily work with children. 100% of teachers say that the areas that develops children are: Identity and autonomy, coexistence, relations with the natural and cultural environment, relations logical / mathematical, language comprehension and expression, artistic expression and body language and motor skills According to the results of the observation guide, the following results were obtained: 85% of boys and girls surveyed have a satisfactory psychomotor development and 15% unsatisfactory. Psychomotor development refers to the psychological and motor maturity that a person, in this case a child. Psychological and motor aspects are the variables that constitute the behavior and attitude. Unlike the intellectual who is given by the maturation of memory, reasoning and the overall process of thought